The Corelation Of Parental Attention To Prosocial Behavior In Group B Children In Paud Segugus Kembang Sepatu Kecamatan Muara Bangkahulu Bengkulu City - Dwi Marseli, Nesa (CV Media Inti Teknologi, 2024)
The purpose of this study was to determine the relationship between parental attention to prosocial behavior of group B children at PAUD Segugus Kembang Sepatu Muara Bangkahulu Subdistrict, Bengkulu City. This research is a correlational research. The population used in this study was 142 children. The number of samples taken by random sampling cluster with a sample of 58 children and parents. The research data analysis was product moment correlation. The results showed parental attention from 4 sub-indicators (guidance and advice, supervision, giving rewards and punishments, and creating a conducive home) with an average value of 3.39 in the very high category and children's prosocial behavior from 4 sub (empathy, sharing, cooperation and care) with an average value of 3.23 in the high category. There is a significant relationship between parental attention and children's prosocial behavior. It is recommended that future researchers look for prosocial behavior factors with other factors including maturity, social status, education and mental capacity.